GLP-1 selectively enhances tonic GABAA receptor-mediated currents in mouse dentate gyrus granule cells of the ventral hippocampus - Netsyk, Olga; Korol, Sergiy V.; Birnir, Bryndis; Jin, Zhe (Frontiers in Cellular Neuroscience, 2025)
Glucagon-like peptide-1 (GLP-1) is a metabolic hormone secreted by L-cells in the gut and it stimulates insulin secretion in the pancreatic islets by activating GLP-1 receptors (GLP-1Rs). In the brain, the GLP-1Rs are expressed in many regions including the hippocampus. We examined whether GLP-1 modulation of GABA-activated currents in the mouse hippocampus varied along the hippocampal dorsal-ventral axis. We recorded spontaneous inhibitory postsynaptic (sIPSCs) and tonic extrasynaptic currents in dorsal and ventral hippocampal dentate gyrus (DG) granule cells in brain slices from 2-month-old mice. GLP-1 (100 pM) did not modulate the GABA-activated fast or slow phasic postsynaptic currents in either the dorsal or the ventral hippocampal slices. In contrast, the tonic extrasynaptic current was potentiated by GLP-1 but, only consistently in the DG granule cells of the ventral hippocampus. Thus, GLP-1 modulation of the DG neurons depends on the dorso-ventral longitudinal hippocampal axis and further, with the subcellular location (synaptic vs. extrasynaptic) of the GABAA receptors (GABAAR) in the DG granule cells. The results are consistent with GLP-1 enhancing the tonic inhibitory extrasynaptic current by a postsynaptic mechanism.